Microbial lactate utilisation and the stability of the gut microbiome - Petra Louis; Sylvia Helen Duncan; Paul Owen Sheridan; Alan William Walker; Harry James Flint (Gut Microbiome, 2022)
The human large intestinal microbiota thrives on dietary carbohydrates that are converted to a range of fermentation products. Short-chain fatty acids (acetate, propionate and butyrate) are the dominant fermentation acids that accumulate to high concentrations in the colon and they have health-promoting effects on the host. Although many gut microbes can also produce lactate, it usually does not accumulate in the healthy gut lumen. This appears largely to be due to the presence of a relatively small number of gut microbes that can utilise lactate and convert it to propionate, butyrate or acetate. There is increasing evidence that these microbes play important roles in maintaining a healthy gut environment. In this review, we will provide an overview of the different microbes involved in lactate metabolism within the gut microbiota, including biochemical pathways utilised and their underlying energetics, as well as regulation of the corresponding genes. We will further discuss the potential consequences of perturbation of the microbiota leading to lactate accumulation in the gut and associated disease states and how lactate-utilising bacteria may be employed to treat such diseases.